Mx1 and Mx2 key antiviral proteins are surprisingly lost in toothed whales - Benjamin Braun; Amir Marcovitz; J. Gray Camp; Robin Jia; Gill Bejerano (2015)
Significance Everybody loves dolphins. And orcas. And Mx (Myxovirus) genes. Mx genes are important immune genes that help mammals fight many RNA and DNA viruses, including HIV, measles, and flu. We make a surprising discovery: dolphins, orcas, and likely all toothed whales lost both Mx genes soon after they diverged from baleen whales and ungulates, which preserve these important genes intact. Because both genes were likely lost simultaneously, we speculate that a viral outbreak exploiting the Mx genes may have forced the toothed whale’s ancestor to sacrifice both. Because the Mx genes are so important, and because all 56 nontoothed whale sequenced mammals carry Mx genes, our discovery makes an important contribution to help preserve these magnificent mammals.